Update for diagnosis and treatment of syndrome after cardiac injury: a mini-review - Lai, Ruihui; Xu, Tan (Frontiers in Cardiovascular Medicine, 2025)
Post-Cardiac Injury Syndrome (PCIS) refers to a collective term encompassing post-myocardial infarction syndrome, post-pericardiotomy syndrome, and post-traumatic pericarditis. With an aging population, the incidence of PCIS is on the rise annually. This condition is considered to be an autoimmune-mediated inflammatory response leading to pericarditis as the primary manifestation of the cardiac disease. Early diagnosis and effective treatment can improve the quality of life and prognosis for PCIS patients. This review aims to provide a comprehensive explicit of the epidemiological characteristics, relevant pathophysiological mechanisms, diagnostic methods, and treatment strategies associated with PCIS, further fostering a deeper understanding and promoting advancements in the prevention and treatment of PCIS.